Domain-aware contrastive learning for ultrasound hip image analysis. (October 2022) - Hareendranathan, Abhilash Rakkunedeth; Tripathi, Arpan; Panicker, Mahesh Raveendranatha; Zhou, Yuyue; Knight, Jessica; Jaremko, Jacob L.
Abstract: Early diagnosis of Developmental Dysplasia of Hip (DDH) using ultrasound can result in simpler and more effective treatment options. Handheld ultrasound probes are ideally suited for such screening due to their low cost and portability. However, images from the pocket-sized probes are of lower quality than conventional probes. Image quality can be enhanced by image translation techniques that generate a pseudo-image mimicking the image quality of conventional probes. This can also help in generalizing the performance of AI-based automatic interpretation techniques to multiple probes. We develop a new domain-aware contrastive unpaired translation (D-CUT) technique for translating between images acquired from different ultrasound probes. Our approach embeds a Bone Probability Map (BPM) as part of the loss function which enforces higher structural similarity around bony regions in the image. Using the D-CUT model we translated 575 images acquired from a Philips Lumify handheld probe to generate pseudo-3D ultrasound (3DUS) images similar (Fréchet Inception Distance = 92) to those acquired from a conventional ultrasound probe (Philips iU22). The pseudo-3DUS images showed high structural similarity (SSIM = 0.68, Cosine Similarity = 0.65) with the original images and improved the contrast around the bony regions. This study establishes the feasibility of using D-CUT to improve the quality of data acquired from handheld ultrasound probes. Among other potential applications, clinical use of this tool could result in wider use of ultrasound for DDH screening programs. Graphical abstract: Image 1 Highlights: Domain-aware image translation to generate high-quality ultrasound images of hip for DDH screening. Improve image quality in Point-Of-Care Ultrasound(POCUS) scanners for wider use in pediatric ultrasound. Ultrasound bone probability map embedded in image translation framework.